DOMESTIC LEGISLATIVE IMPROVEMENT ASSOCIATED TO THE SUBJECTS OF OPERATIONAL-SEARCH ACTIVITY ON A NON-PUBLIC PRINCIPLES - Zholdibay, Uspanov; Dana, Tyrarbayeva (International Journal of Research -GRANTHAALAYAH, 2019)
In the article prepared by the Vice-Rector for Science and International Relations, Candidate of Juridical Science, Professor Uspanovov Zh. discovers the issues of legal support on assistance of citizens to the bodies carrying out operational search activities. In its current definition and regulation of operational search legislation has a mixed legal nature; it cannot be considered as an employment contract, such relations are not civil law relations, they are of administrative and managerial nature. Considering that an important component of legal support, in addition to defining the mutual rights and obligations of the parties, is that its presence enables the person assisting law enforcement agencies to openly protect, including in court, their social, labor and other rights, legal support must be attributed to the contract for the provision of paid information services.